Long, A. A. (2015). Greek Models of Mind and Self. Cambridge (MA), London, Harvard University Press - Proscurcin Junior , Pedro (Revista Archai, 2025)
Long, A. A. (2015). Greek Models of Mind and Self. Cambridge (MA), London, Harvard University Press